2014
DOI: 10.1186/1471-2369-15-130
|View full text |Cite
|
Sign up to set email alerts
|

The influence of vitamin D analogs on calcification modulators, N-terminal pro-B-type natriuretic peptide and inflammatory markers in hemodialysis patients: a randomized crossover study

Abstract: BackgroundThe risk of cardiovascular disease is tremendously high in dialysis patients. Dialysis patients treated with vitamin D analogs show decreased cardiovascular morbidity and mortality compared with untreated patients. We examined the influence of two common vitamin D analogs, alfacalcidol and paricalcitol, on important cardiovascular biomarkers in hemodialysis patients. Anti-inflammatory effects and the influence on regulators of vascular calcification as well as markers of heart failure were examined.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 57 publications
3
13
1
2
Order By: Relevance
“…In the present study, additional analysis revealed that there were no significant differences in NT-proBNP, CRP levels, and PTH levels between patients with and without vitamin D supplements or analogues treatment. Even though several previous studies showed that stimulation of vitamin D receptors reduced BNP levels, 46 51 some recent published data demonstrated that there was no significant association between vitamin D supplements and NT-proBNP concentrations in dialysis patients, 52 54 supporting the results of the present study.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, additional analysis revealed that there were no significant differences in NT-proBNP, CRP levels, and PTH levels between patients with and without vitamin D supplements or analogues treatment. Even though several previous studies showed that stimulation of vitamin D receptors reduced BNP levels, 46 51 some recent published data demonstrated that there was no significant association between vitamin D supplements and NT-proBNP concentrations in dialysis patients, 52 54 supporting the results of the present study.…”
Section: Discussionsupporting
confidence: 84%
“…There are positive correlations between low 25-hydroxyvitamin D [25(OH)D; < 43 nmol/L] and obesity [ 10 ] as well as between 25(OH)D < 33–37.5 nmol/L and cardiovascular mortality [ 11 ]. Vitamin D has a protective effect on bones [ 12 ], anticancer [ 13 ] and anti inflammatory [ 14 ] effects and its receptors are present in pancreatic b cells and insulin sensitive tissues including skeletal muscle tissues [ 15 ]. Vitamin D repletion improves insulin and glucose homeostasis in animal models of vitamin D deficiency [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stubbs et al reported that cholecalciferol supplementation altered calcitriol-responsive monocyte proteins and decreased inflammatory cytokines in 7 HD patients [79]. Conversely, recent randomized crossover trial did not find differences in IL-6, TNF-α and CRP following vitamin D analogs supplementation in chronic HD patients [80]. …”
Section: Correction Of Inflammation In Ckdmentioning
confidence: 99%